Territoire, innovation et développement durable : l'émergence d'un nouveau régime conventionnel? - Buclet, Nicolas (Revue d'Économie Régionale & urbaine, 2011)
ENG TITLE: Territory, innovation and sustainable development: towards a new conventional regime? ABSTRACT: The paper examines the increasing number of diverse local development initiatives around the world aiming to break away from the predominant economic system. These initiatives, we argue, despite a somewhat visible disparity, largely rest on relatively similar principles, values and references. We argue that they are effectively laying the foundation for a new conventional regime more attuned to sustainable development goals. The paper analyses the characteristics of this regime, which refuses market dominance and favours reciprocal exchanges, as defined by Karl Polanyi. It is, nevertheless, necessary to question the potential and limitations of this conventional regime. (English)
Keywords: Territoire; conventions; development economics; développement durable; economic development; economics; environment; innovation; mathematical models; sustainable development; territory

Toward a new countermovement: a framework for interpreting the contradictory interventions of migrant civil society organizations in urban labor markets - Martin, Nina (Environment & Planning A, 2011)
Low-wage migrant workers in the United States confront a perilous labor market, where wages are low, the risk of injury on the job is high, and the fear of apprehension by immigration authorities is widespread. There is increasing empirical evidence that civil society organizations are becoming involved in mediating labor-market problems, but work remains to be done in developing a robust theoretical conception of why such organizations are involved in this arena and how we might evaluate the impacts of their interventions. This paper presents a framework for interpreting the role of migrant civil society organizations as labor-market intermediaries, by extending Karl Polanyi's theory of the 'double movement' and more recent writing to neoliberalism and precarious work. On the basis of data collected from migrant nonprofit organizations in Chicago, I theorize migrant civil society organizations as part of the creation of a new countermovement that protects the interests of both workers and employers from the destructive nature of an unregulated labor market, as predicted by Polanyi. I catalogue organizations' responses to precarious work and create a generalizable framework for evaluating the contingent outcomes of their strategies. Organizations' work is interpreted as complex and sometimes contradictory: the potential to shield workers and advocate for progressive change is in constant tension with the neoliberal patterns of state and economic restructuring that such organizations can support.
Keywords: United States; civil society; immigrants; industrial mediation; labour market; migrant labor; migrant labour; neoliberalism; salaries, wages, etc.; societies, etc.

Nature, Capital and Neighborhoods: 'Dispossession without Accumulation'? - Kappeler, Aaron; Bigger, Patrick (Antipode, 2011)
The ongoing economic crisis, which originated in the USA and has since spread rapidly to capital markets worldwide, is massive, complex, and many times contradictory. One could say the same for responses to the crisis as governments, firms and multi-national institutions struggle to grasp the full magnitude of the event. This article interrogates the key commodities involved-land, labor and money-and the always-uneasy relations between spaces of social reproduction and capital. Such ambivalence is critical to understanding how new economic realities are formed in light of retreating neoliberalism as markets become destabilized. The analysis provided suggests the commodities involved in the housing crisis are the basis for a countermovement against dispossession.
Keywords: MARX, Karl, 1818-1883; United States; capital market; capitalism; housing market; international business enterprises; labor; labour; mixed economy; neoliberalism; social aspects

Grounding Globalization: Labour in the Age of Insecurity - Webster, Edward; Lambert, Rob; Beziudenhout, Andries (John Wiley & Sons, 2011)
*Winner of the 2009 Distinguished Scholarly Monograph Prize, awarded by the American Sociological Association Labor and Labor Movements section* Claims have been made on the emergence of a new labour internationalism in response to the growing insecurity created by globalization. However, when persons face conditions of insecurity they often turn inwards. The book contains a warning and a sign of hope. Some workers become fatalistic, even xenophobic. Others are attempting to globalize their own struggles. Examines the claim that a new labour internationalism is emerging by grounding the book in evidence, rather than assertion Analyzes three distinct places – Orange, Australia; Changwon, South Korea; and Ezakheni, South Africa – and how they dealt with manufacturing plants undergoing restructuring Explores worker responses to rising levels of insecurity and examines preconditions for the emergence of counter-movements to such insecurities Highlights the significance of 'place' and 'scale', and demonstrates how the restructuring of multi-national corporations, and worker responses to this, connect the two concepts
Keywords: Polanyi problem; critique; globalization; internationalism; labour; science / earth sciences / geography

Food crises, food regimes and food movements: rumblings of reform or tides of transformation? - Holt Gimenez, Eric; Shattuck, Annie (Journal of Peasant Studies, 2011)
This article addresses the potential for food movements to bring about substantive changes to the current global food system. After describing the current corporate food regime, we apply Karl Polanyi's 'double-movement' thesis on capitalism to explain the regime's trends of neoliberalism and reform. Using the global food crisis as a point of departure, we introduce a comparative analytical framework for different political and social trends within the corporate food regime and global food movements, characterizing them as 'Neoliberal', 'Reformist', 'Progressive', and 'Radical', respectively, and describe each trend based on its discourse, model, and key actors, approach to the food crisis, and key documents. After a discussion of class, political permeability, and tensions within the food movements, we suggest that the current food crisis offers opportunities for strategic alliances between Progressive and Radical trends within the food movement. We conclude that while the food crisis has brought a retrenchment of neoliberalization and weak calls for reform, the worldwide growth of food movements directly and indirectly challenge the legitimacy and hegemony of the corporate food regime. Regime change will require sustained pressure from a strong global food movement, built on durable alliances between Progressive and Radical trends.
Keywords: corporate food regime; corporations; food movements; food prices; food security; food sovereignty; food supply; global food crisis; hunger; neoliberalism; peasant studies; right to food; social change; strategic alliances (business)